Fictitious Capital Silk, Cotton, and the Rise of the Arabic Novel - Holt, Elizabeth M. (Fordham University Press, 2017)
The ups and downs of silk, cotton, and stocks syncopated with serialized novels in the late-nineteenth-century Arabic press: Time itself was changing. Novels of debt, dissimulation, and risk begin to appear in Arabic at a moment when France and Britain were unseating the Ottoman legacy in Beirut, Cairo, and beyond. Amid booms and crashes, serialized Arabic fiction and finance at once tell the other’s story.While scholars of Arabic often write of a Nahdah, a sense of renaissance, Fictitious Capital argues instead that we read the trope of Nahdah as Walter Benjamin might have, as "one of the monuments of the bourgeoisie that [are] already in ruins." Financial speculation engendered an anxious mixture of hope and fear formally expressed in the mingling of financial news and serialized novels in such Arabic journals as Al-Jinān, Al-Muqtataf, and Al-Hilāl. Holt recasts the historiography of the Nahdah, showing its sense of rise and renaissance to be a utopian, imperially mediated narrative of capital that encrypted its inevitable counterpart, capital flight
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jul 2020)
Keywords: Arabic Novel; Beirut; Cairo; Jurjī Zaydān; Khalīl al-Khūrī; Nahdah; Salīm al-Bustānī; Yaʿqūb Ṣarrūf; capitalism; cotton; silk; LITERARY CRITICISM / Middle Eastern; Arabic fiction -- 19th century -- History and criticism; Literature publishing -- Economic aspects -- Egypt -- History -- 19th century; Literature publishing -- Economic aspects -- Lebanon -- History -- 19th century; Serialized fiction -- Egypt -- History and criticism; Serialized fiction -- Lebanon -- History and criticism